Carbon Emission Disclosure and Financial Performance of Quoted Nigerian Financial Services Companies - Emmanuel, Yinka Lydia; Adenikinju, Olayinka; Doorasamy, Mishelle; Ayoola, Tajueden John; Oladejo, Abiodun Oyebamiji; Kwarbai, Jerry D.; Otekunrin, Adegbola Olubukola (International Journal of Energy Economics and Policy, 2023)
Countries and businesses all over the world are focusing on initiatives to safeguard the environment. The goal of stabilizing greenhouse gas concentrations at a level that would preclude harmful anthropogenic interaction with the climate system is a key topic of focus during numerous endeavours. This study examined the relationship between the financial performances of quoted Nigerian financial services companies and carbon emission disclosure. The study employed ex-post facto research design and secondary data from the annual report of quoted Nigerian financial services companies. Multiple regression analysis was on a panel data set. Results show the variable that significantly returns on equity are ‘other indirect emission’ disclosure -scope 3 (coefficient = 0.416 and probability = 0.087), firm size (coefficient = 0.191 and probability = 0.089), capital intensity (coefficient = 0.000149 and probability = 0.000) and growth (coefficient = -0.0258 and probability = 0.014). The impact of other indirect emission disclosure -scope 3 on return on equity is positive and statistically significant. Also, the result shows the variable that significantly influences the return on sales are ‘other indirect emission’ disclosure -scope 3(coefficient = 0.790 and probability =0.001), firm size (coefficient = -0.395 and probability = 0.053), capital intensity (coefficient =0.000194 and probability =0.001) and growth (coefficient = 0.0360 and probability = 0.073). It was discovered that other indirect emission disclosure – scope 3 has a positive and significant effect on financial performance (ROE and ROS). This study concluded that carbon emission disclosure significantly influences the return on equity of the selected quoted Nigerian financial services companies. Also, the study concluded that carbon emission disclosure significantly influences the return on sales of the selected quoted Nigerian financial services companies.